AN EXPERIMENTAL DETERMINATION OF PERFORMANCE ECO-WASTE CERAMIC COMPOSITE UNDER SINTERING CONTROLLED: STABILITY, HARDNESS AND ACOUSTIC MEASUREMENT - Shamsudin, Z.; Mesri, M.; Zuhaimi, A.K.; Hassan, R.; Mulyadi, M. (Journal of Advanced Manufacturing Technology (JAMT), 2022)
The filler loading input plays a key role on physico-mechanical of eco-waste ceramic composite (ECC) under controlled heat treatment. In this study, the addition cockleshell (CS) in soda lime silicate glass (SLSG) was fabricated to investigate the effect of filler loading at different sintering temperature. The selected temperatures were in range between 700 and 850 °C with 2 °C/min heating rate at constant holding time. The ECC was formed with the inclusion of CS as filler between 0 to 50 wt%. The performance of ECCs were subjected to stability test, hardness test while the modulus was measured via acoustic measurement. The results showed that addition 30 wt % of CS filler had outstanding physical and mechanical qualities at 850 °C where apparent porosity and water absorption reduced, which leads to bulk density increased. This indicated that the difference in properties acquired by different heat treatments and filler loading. This suggested that sintering controlled, and filler loading were the result of the performance of ECC as a potential material for structural enhancement in the building application.